Qualidade das silagens de sorgo reensiladas com e sem inoculante microbiano - Pedro Henrique Fulgêncio Michel (2015)
The silage is the main forage conservation method used in the Brazil. Among the plants used, the sorghum stands out mainly due its significant water deficit tolerance, high forage productivity and possibility of using regrowth. The oxygen entry in the silo after opening is harmful to forage conservation because it favors yeasts and molds growth. These microbes degrade soluble carbohydrates and lactic acid producing heat and increasing pH. In order to improve the fermentative process and avoid aerobic degradation, several inoculants have been used. However, studies with these products in re-ensiled silages are still scarce. This study aimed to determine the effect of re-ensiling and the use of microbial inoculants on the quality of sorghum silage. The sorghum hybrid BRS 655 was harvested and ensiled with or without an inoculant containing Lactobacillus plantarum e Propionibacterium acidipropionici at the ensiling time. After 56 days of the ensiling, the treatment re-ensiling was deployed so that the material was removed e re-ensiled after 24 hours of exposure to air. Gases and effluents losses and total dry matter were not changed by the inoculant. Similar results were obtained for the gases and total dry matter losses at re-ensiling process. However, the effluents losses were higher in the re-ensiled silages. The inoculant use and re-ensiling process did not affect the fermentation parameters, chemical composition and microbial count in the silo opening. The in vitro digestibity of dry matter was not favored by inoculant, but was higher to the silages which were not re-ensiled. The aerobic stability was not altered by inoculants use, however, the re-ensiled silages remained stable for longer time. The microbial count at the loss aerobic stability time was not influenced by the inoculants and re-ensiling. The re-ensiling of sorghum silage after 24 hours of exposure to air did not change the silage quality, but increased the effluents losses and reduced the in vitro dry matter digestibility. The inoculants use did not influence the sorghum silage quality.